ANALYSIS OF THE RELATIONSHIP BETWEEN ELECTRONIC MONEY (E-MONEY) AND MONEY SUPPLY IN INDONESIA (2011–2019) - Kartiko Dhian Pramono; Estu Wijaya (Jurnal Ekonomi Trisakti, 2022)
This study aims to analyze the relationship between electronic money (e-money) and money supply in Indonesia. The data used is electronic money, APMKand the money supply using cointegration test analysis to determine the long-term balance relationship, and granger causality test to determine the reciprocal relationships between variables. The results of the analysis show that the variables of electronic money and the money supply have a long-term balance and between electronic money variables and the money supply only have a one-way causality relationship.